2019
DOI: 10.3390/ijerph16203966
|View full text |Cite
|
Sign up to set email alerts
|

Spatial-Temporal Variation of Bacterial Communities in Sediments in Lake Chaohu, a Large, Shallow Eutrophic Lake in China

Abstract: Sediment bacterial communities are critical for the circulation of nutrients in lake ecosystems. However, the bacterial community function and co-occurrence models of lakes have not been studied in depth. In this study, we observed significant seasonal changes and non-significant spatial changes in the beta diversity and community structure of sediment bacteria in Lake Chaohu. Through linear discriminant analysis effect size (LEfSe), we observed that certain taxa (from phylum to genus) have consistent enrichme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 91 publications
(97 reference statements)
0
13
0
Order By: Relevance
“…Chthoniobacterales are very common in soils ( Sangwan et al, 2004 ) and can make rapid responses to changes in the availability of substrates and oxygen in soil ( Hirsch et al, 2017 ). Pedosphaeraceae has been identified as an important species in soil biogeochemical cycle, yet a better understanding of their roles in soil bacterial co-occurrence networks is still needed in the future ( Zhang et al, 2019 ). However, a recent study revealed that Bryobacter , GR-WP33-30, and Rhizomicrobium were the keystone karst bacteria in Fuyuan County, Yunnan Province ( Xue et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chthoniobacterales are very common in soils ( Sangwan et al, 2004 ) and can make rapid responses to changes in the availability of substrates and oxygen in soil ( Hirsch et al, 2017 ). Pedosphaeraceae has been identified as an important species in soil biogeochemical cycle, yet a better understanding of their roles in soil bacterial co-occurrence networks is still needed in the future ( Zhang et al, 2019 ). However, a recent study revealed that Bryobacter , GR-WP33-30, and Rhizomicrobium were the keystone karst bacteria in Fuyuan County, Yunnan Province ( Xue et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, in the first phylum, unknown members of the methanogenic Anaerolineaceae family (3-3.7%), while in the latter, unknown members of the Pedosphaeraceae family were detectable in a significant amount. These two families were widely distributed in the benthic communities of a large shallow eutrophic lake in China [53].…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, a high-throughput sequencing (HTS) approach can provide a more accurate analysis of the denitrifier community in complex ecosystems. To date, this analysis has been widely used to investigate denitrifier communities in various ecosystems, such as lake water and sediment, soil, and river periphytic biofilms [ 31 , 32 , 33 , 34 ]. However, there is still a lack of studies on applying the HTS approach to investigate the denitrifier community in CWs.…”
Section: Introductionmentioning
confidence: 99%